Sonographic and Elastographic Features of Extra- and Intrathyroidal Ectopic Thymus Mimicking Malignancy: Differential Diagnosis in Children - Stasiak, Magdalena; Adamczewski, Zbigniew; Stawerska, Renata; Krawczyk, Tomasz; Tomaszewska, Monika; Lewiński, Andrzej (Frontiers in Endocrinology, 2019)
Thyroid nodules with ultrasound (US) cancer risk features and extra-thyroid lesions suggesting malignant lymph nodes, require prompt diagnosis, especially in children. The US pattern of intrathyroidal ectopic thymus (IET) can strongly suggest papillary thyroid carcinoma (PTC). The extra-thyroid ectopic thymic tissue (EET) can mimic pathological lymph nodes in US. The aim of the study has been to demonstrate US features and diagnostic methods, allowing finally to confirm the presence of IET and EET in children. The US and elastographic features of 16 ectopic thymic tissue (ET) lesions were analyzed so as to describe the typical characteristics of ET and to define the best method to differentiate ET and malignant lesions. Among 16 analyzed lesions, 11 lesions were IET, and 5 were EET adjacent to the thyroid connective tissue capsule. Most of IET were located in the middle part of the right lobe and were fusiform or oval in shape. All the lesions were solid, hypoechoic, and heterogeneous with bright internal echoes. Among IET, 73% of lesions had well- or very well-defined margins. In strain elastography of IET lesions, the strain ratio was similar in all lesions, and its value ranged from 0.95 to 1.09. Despite the low prevalence of IET and cervical EET, clinicians and radiologists should be aware of US characteristics of such lesions. The confirmation of their benign character is absolutely required. Elastography is a useful tool to initially differentiate PTC and IET. However, due to high risk of malignancy in thyroid lesions in children, similarity of US features of PTC and IET, and due to the possibility of malignancy in ET, only cytological evaluation provides definitive diagnosis.